2010
DOI: 10.1089/vbz.2009.0206
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Tacaribe Serocomplex Viruses (FamilyArenaviridae, GenusArenavirus) in Cricetid Rodents from New Mexico, Texas, and Mexico

Abstract: Blood samples from 4893 cricetid rodents were tested for antibody (immunoglobulin G) to Whitewater Arroyo virus and Amaparí virus to extend our knowledge of the natural host range and geographical distribution of Tacaribe serocomplex viruses in North America. Antibodies to arenaviruses were found in northern pygmy mice (Baiomys taylori), woodrats (Neotoma spp.), northern grasshopper mice (Onychomys leucogaster), oryzomys (Oryzomys spp.), deermice (Megadontomys nelsoni and Peromyscus spp.), harvest mice (Reithr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Subsequently, WWAV was isolated from woodrats (presumed to be Neotoma albigula ) captured in northwestern New Mexico (Fulhorst et al 1996); Tacaribe serocomplex viruses were isolated from white-throated woodrats ( N. albigula ), a bushy-tailed woodrat ( N. cinerea ), Mexican woodrats ( N. mexicana ), large-eared woodrats ( N. macrotis ), southern plains woodrats ( N. micropus ), and California mice ( Peromyscus californicus ) captured at other localities in the United States (Cajimat et al 2007b, 2008; Fulhorst et al 2001, 2002a, 2002b; Milazzo et al 2008); antibodies (IgG) to Tacaribe serocomplex viruses were found in cricetid rodents captured in San Luis Potosí and 9 other states in Mexico (Milazzo et al 2010); and RNA of RCTV was found in white-toothed woodrats ( N. leucodon ) captured in San Luis Potosí (Inizan et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, WWAV was isolated from woodrats (presumed to be Neotoma albigula ) captured in northwestern New Mexico (Fulhorst et al 1996); Tacaribe serocomplex viruses were isolated from white-throated woodrats ( N. albigula ), a bushy-tailed woodrat ( N. cinerea ), Mexican woodrats ( N. mexicana ), large-eared woodrats ( N. macrotis ), southern plains woodrats ( N. micropus ), and California mice ( Peromyscus californicus ) captured at other localities in the United States (Cajimat et al 2007b, 2008; Fulhorst et al 2001, 2002a, 2002b; Milazzo et al 2008); antibodies (IgG) to Tacaribe serocomplex viruses were found in cricetid rodents captured in San Luis Potosí and 9 other states in Mexico (Milazzo et al 2010); and RNA of RCTV was found in white-toothed woodrats ( N. leucodon ) captured in San Luis Potosí (Inizan et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Examination of more than 2,000 mammals, principally small rodents, in Trinidad at that time failed to provide serological evidence of infection with TCRV, leading to the suggestion that artibeus bats were reservoirs of TCRV (11). This is unusual in that all other arenaviruses with known hosts are rodent borne (12,16). When TCRV was isolated from artibeus fruit bats, it was observed that some appeared healthy while others were mistaken for rabid bats (11).…”
mentioning
confidence: 99%
“…Blood samples from the rodents from FBMB, FLOM, AFTN, and MSSP were tested in previous studies (Milazzo et al 2010, Mauldin et al 2013) for immunoglobulin G (IgG) to WWAV strain AV 9310135 (Fulhorst et al 1996), using an ELISA (Bennett et al 2000). The test antigen was prepared from Vero E6 cells infected with AV 9310135, the control (comparison) antigen was prepared from uninfected Vero E6 cells, and the working dilutions of the antigens were determined by box-titration against immune sera from white-throated woodrats ( N. albigula ) inoculated with AV 9310135 (Fulhorst et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies revealed a high level of genetic diversity among Tacaribe serocomplex viruses associated with N. albigula in Arizona and New Mexico (Milazzo et al 2008); a high level of genetic diversity among Tacaribe serocomplex viruses associated with N. mexicana in Arizona, Colorado, New Mexico, and Utah (Cajimat et al 2008); and evidence of arenaviral infections in southern plains woodrats captured in Colorado, New Mexico, Oklahoma, and Texas (Cajimat et al 2011, Calisher et al 2001, Fulhorst et al 2002, Milazzo et al 2010). The purpose of this study was to extend our knowledge of the genetic diversity among Tacaribe serocomplex viruses associated with N. micropus and to define better the natural host relationships of these viruses.…”
Section: Introductionmentioning
confidence: 99%